2003
DOI: 10.1124/mol.63.4.777
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nucleotide Regulation of Epithelial Chloride Transport in the Jejunum of P2Y4-Null Mice

Abstract: The P2Y 4 receptor is responsive to UTP in human and to ATP and UTP in rodents. With the aim of identifying its pharmacotherapeutic interest, we generated P2Y 4 -null mice by a classic gene targeting method. The proportion of genotypes was consistent with X-linked Mendelian transmission. Gene inactivation was checked by the complete disappearance of P2Y 4 receptor mRNA from liver, stomach, and intestine. The P2Y 4 -null mice had a grossly normal behavior, growth, and reproduction. Chloride secretion by the jej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 28 publications
2
71
0
Order By: Relevance
“…The persistence of a Cl -secretory response to UTP or ATP in P2Y 2 -/-mice suggested that the response in mice could be mediated by P2Y 4 receptors [32]. Indeed, loss of nucleotide regulation of epithelial chloride transport occurs in the jejunum of P2Y 4 -null mice [90]. P2Y 4 mRNA are expressed in rat and guinea pig submucosa [17,18,27], murine colonic crypts [75], stomach and intestine [90,105], and more recently in enteric glial cells [108,109].…”
Section: Enac and Cftr Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The persistence of a Cl -secretory response to UTP or ATP in P2Y 2 -/-mice suggested that the response in mice could be mediated by P2Y 4 receptors [32]. Indeed, loss of nucleotide regulation of epithelial chloride transport occurs in the jejunum of P2Y 4 -null mice [90]. P2Y 4 mRNA are expressed in rat and guinea pig submucosa [17,18,27], murine colonic crypts [75], stomach and intestine [90,105], and more recently in enteric glial cells [108,109].…”
Section: Enac and Cftr Channelsmentioning
confidence: 99%
“…P2Y 2 and P2Y 4 receptors are very prevalent luminal receptors involved in Cl -, HCO 3 -, K + secretion, or mucin secretion. Nucleotide stimulation of K + secretion occurs in the distal colon, K + secretion and HCO 3 -secretion in the gallbladder (Table 3; [17,18,75,90]); HCO 3 -secretion also occurs in ducts and is involved in the formation of pancreatic juice. Stimulation of Cl -secretion occurs in the gallbladder, small intestine, and duct cells.…”
Section: Enac and Cftr Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential effects of apical and basolateral UTP on intestinal epithelial Cl − secretion have been described [626]. There is a loss of regulation of Cl − transport by ATP and UTP in the jejunum of P2Y 4 -null mice [580]. Cuthbert and Hickman [165] confirmed the earlier reports about the effects of ATP on transepithelial ion transport but, since they found that TTX virtually abolished the effects of ATP on electrogenic chloride secretion, they suggested that the effects of ATP were indirect, via neural elements in the intramural plexus.…”
Section: Intestinal Secretionmentioning
confidence: 99%
“…Using a knockout model for the P2Y2 receptor, Cressman et al demonstrated impaired Cl − secretion in airway and gallbladder epithelium, but not in tissue from the jejunum [47]. Other receptors have also been shown to regulate chloride conductance including P2Y4 in intestinal epithelia [48,49] and the UDP receptor P2Y6 in bronchial epithelium [50]. P2Y2 receptor-induced Cl − secretion results from increased intracellular Ca 2+ concentration leading to activation of Ca 2+ -activated Cl − channels.…”
Section: Chloride Secretionmentioning
confidence: 99%